2016
DOI: 10.1016/j.brainres.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in human photoreceptor diseases

Abstract: Photoreceptors are specialized sensory neurons essential for light detection in the human eye. Photoreceptor cell dysfunction and death cause vision loss in many eye diseases such as retinitis pigmentosa and achromatopsia. Endoplasmic reticulum (ER) stress and Unfolded Protein Response (UPR) signaling have been implicated in the development and pathology of heritable forms of retinitis pigmentosa and achromatopsia. We review the role of ER stress and UPR in retinitis pigmentosa arising from misfolded rhodopsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…The involvement of the ERS has been increasingly recognized as a contributor in a variety of diseases, including glaucoma [52], DR [53], AMD [54] and RP [55]. GRP78, a protein chaperone, was chosen as the ERS marker in the present experiment [56].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the ERS has been increasingly recognized as a contributor in a variety of diseases, including glaucoma [52], DR [53], AMD [54] and RP [55]. GRP78, a protein chaperone, was chosen as the ERS marker in the present experiment [56].…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of ER stress also protects injured neurons and improves functional recovery in experimental spinal cord injury, 44 , 45 stroke, 46 Alzheimer disease, 47 tauopathies, 48 Parkinson’s disease, 49 amyotrophic lateral sclerosis, 50 , 51 prion disease 52 , 53 , 54 and, most relevantly, retinal cell degenerations, including RGC 18 , 19 and photoreceptor. 12 , 16 , 55 , 56 Importantly, recent reports provide evidence of ER stress in brain and spinal cord lesions of human MS patients 24 and rodent EAE, 25 suggesting the importance of ER stress in the pathophysiology of MS. However, previous studies showed that PERK activation in oligodendrocytes promotes their survival in EAE, 39 , 57 and suggest that ER stress in oligodendrocytes is beneficial in demyelinating diseases.…”
Section: Discussionmentioning
confidence: 99%
“…11,21 Chronic ER stress induces cell death and thus may contribute to the cone dysfunction and vision loss observed in patients with ATF6 mutations. 22,23,16 Taking into account the fact that the overlapping clinical symptoms of different IRD procure choosing the proper genes for nucleotide sequence analysis, it seems reasonable to add the ATF6 gene to a list of so-called 'retinal genes' analysed by NGS methods.…”
Section: Discussionmentioning
confidence: 99%